1973
DOI: 10.1139/e73-071
|View full text |Cite
|
Sign up to set email alerts
|

Palynology of the Great Lakes: The Surface Sediments of Lake Ontario

Abstract: Pollen was analyzed in the surface 1 cm of sediment taken from 90 sample stations collected in 1968 from a 16 km grid on Lake Ontario. Sixty-nine taxa were identified and the more abundant taxa subjected to trend surface analysis. Pollen concentration in 60 samples ranged up to 240 000 grains per g dry sediment with tho higher concentration in the offshore silt and clay sediments of the basins. Pollen percentages of 80 stations were based on 100 a r more tree pollen with the average percentage values above 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Most lakes have inflowing rivers, so waterborne pollen may also make a substantial contribution to the pollen influx to the lake (McAndrews and Power, 1973;Peck, 1973Peck, , 1974Bonny, 1978;Sun and Wu, 1987;Traverse, 1992;Huang et al, 2004;Xu et al, 2005;Brown et al, 2007). In order to attempt quantitative reconstructions of past vegetation and paleoclimate from the sedimentary record in such lakes, it is important to understand the relative importance of the different components of the pollen taphonomy and to characterize the spatial sensitivity of the record, the pollen source area.…”
Section: Introductionmentioning
confidence: 99%
“…Most lakes have inflowing rivers, so waterborne pollen may also make a substantial contribution to the pollen influx to the lake (McAndrews and Power, 1973;Peck, 1973Peck, , 1974Bonny, 1978;Sun and Wu, 1987;Traverse, 1992;Huang et al, 2004;Xu et al, 2005;Brown et al, 2007). In order to attempt quantitative reconstructions of past vegetation and paleoclimate from the sedimentary record in such lakes, it is important to understand the relative importance of the different components of the pollen taphonomy and to characterize the spatial sensitivity of the record, the pollen source area.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the majority of pollen and spores entering most medium-sized and larger lakes and near-shore marine sediments are fluvially transported from river catchments (Federova, 1952;Peck, 1973;McAndrews and Power, 1973;Crowder and Cuddy, 1973;Pennington, 1979;Bonny, 1980;Brown, 1985;David and Roberts, 1990;Traverse, 1992Traverse, , 1994 and that the ratio of fluvial to airborne (both wet and dry) input depends on the relationship between the size of the catchment, the lake surface area, the topography and the catchment vegetation. In classic studies, Peck (1973Peck ( , 1974 found 97% of the pollen and spore input to Oakdale reservoir was fluvial and Bonny (1978) found 87% of the input to Blelham Tarn was of fluvial origin.…”
Section: Introductionmentioning
confidence: 99%
“…Small lake core sites in the Georgian Bay drainage basin are indicated by triangles and nearby climate stations by circles. The pollen diagram for Edward Lake is in McAndrews and Manville (1987) and that for Axe Lake is in McCarthy et al (2007). The subregions of the Great Lakes-St. Lawrence Forest bordering Georgian Bay and the North Channel are shown, following Rowe (1972): L.1-Huron-Ontario; L.4d-Georgian Bay, and L.10-Algoma.…”
Section: Georgian Bay: Hydrology and Paleohydrologymentioning
confidence: 99%